PENGARUH DIVERSITAS GENDER PADA STRUKTUR DEWAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi empiris pada perusahaan manufaktur yang terdaftar di BEI tahun 2015-2017) - Vina Dwi Maghfiroh (Diponegoro Journal of Accounting, 2019)
This study aims to examine how the influence of gender diversity on the board structure on the company's financial performance. Gender diversity in the board structure as an independent variable is measured by two proxies, namely the dummy variable of the existence of women in the board structure and the proportion of women in the board structure. While financial financial performance as the dependent variable is measured by looking at the value of ROA as a measure of accounting-based and Tobin’s Q as a market-based measure. In this study also used control variables, including board size, board independence, company size, and leverage. The sample used in this study was selected using a purposive sampling method in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The final sample obtained was 367 samples from 131 companies. Hypothesis testing is done using panel data regression analysis. The results of statistical tests show that gender diversity in the board structure does not significantly influence the company's financial performance.